2015
DOI: 10.7567/apex.8.045501
|View full text |Cite
|
Sign up to set email alerts
|

Selective crystallization of the metastable phase of indomethacin at the interface of liquid/air bubble induced by femtosecond laser irradiation

Abstract: We describe a new method for the selective crystallization of the metastable phase (α-form) of indomethacin. To obtain the α-form, we prepared a highly supersaturated solution and then introduced forcible nucleation techniques, namely, laser irradiation and magnetic stirring. When the laser irradiated near the side wall, the α-form crystallized within 24 h. The α-form crystals showed temporal stability for at least 8 months in air ambient at room temperature. We conclude that control of the laser irradiation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…Furthermore, it is known that flows and interfaces work effectively for crystallization. For examples, crystallization of proteins and small organic molecules that are pharmaceutical compounds is promoted by a flow and gas-liquid interface by laser or ultrasonic irradiations [5][6][7][8][9][10]. In this study, we report the crystallization of acetaminophen using the liquid-liquid interface phenomenon by a microchannel.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, it is known that flows and interfaces work effectively for crystallization. For examples, crystallization of proteins and small organic molecules that are pharmaceutical compounds is promoted by a flow and gas-liquid interface by laser or ultrasonic irradiations [5][6][7][8][9][10]. In this study, we report the crystallization of acetaminophen using the liquid-liquid interface phenomenon by a microchannel.…”
Section: Introductionmentioning
confidence: 95%
“…Ultrasound can be applied to alter the polymorph distribution of molecular crystals, which is attributed to the ultrasound-induced local disturbance of supersaturation and cooling rate. ,, In recent years, laser-induced crystallization has also been found to affect the polymorphism of some organic crystals. It has been reported that crystal polymorphism can be controlled by laser-induced electromagnetic fields and laser-induced cavitation bubbles. ,, Nanosecond laser irradiation with different polarization will enhance the proportion of specific polymorphs. ,,, The femtosecond laser can be used to control the crystallization results with different laser-induced phenomenon since it can be directly absorbed by the solution. A focused femtosecond laser will induce cavitation bubbles that can result in the change of polymorphism. ,, Although some specific approaches have been reported, however, the control of the laser-induced crystallization still faces challenges.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that crystal polymorphism can be controlled by laser-induced electromagnetic fields and laser-induced cavitation bubbles. ,, Nanosecond laser irradiation with different polarization will enhance the proportion of specific polymorphs. ,,, The femtosecond laser can be used to control the crystallization results with different laser-induced phenomenon since it can be directly absorbed by the solution. A focused femtosecond laser will induce cavitation bubbles that can result in the change of polymorphism. ,, Although some specific approaches have been reported, however, the control of the laser-induced crystallization still faces challenges. The understanding of the femtosecond laser-induced nucleation process is necessary to help improve these methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using focused femtosecond laser pulses, where sufficient power can be delivered to the system for optical breakdown and laser-induced cavitation, selective formation of metastable polymorphs of indomethacin and aspirin were demonstrated by Maruyama and co-workers. 41,42 Wang et al also succeeded in increasing the percentage of metastable forms II and III of paracetamol from less than 10% to more than 40% using focused femtosecond pulses. 43 A versatile technique is laser-trapping crystallization, as developed by Masuhara, Sugiyama and co-workers, in which a continuous-wave (CW) laser beam is focused at a solution-air interface.…”
Section: Introductionmentioning
confidence: 99%